ChemInform Abstract: Synthesis of Selective Inhibitors of Sphingosine Kinase 1. Issue 25 (3rd June 2013) - Baek, Dong Jae; MacRitchie, Neil; Pyne, Nigel J.; Pyne, Susan; Bittman, Robert
Abstract Among the novel compounds screened for their inhibitory potency against sphingosine kinase 1, derivative (IIIb) exhibits the highest activity.